Benefits, problems, and optimal timing of administration of indocyanine green fluorescence cholangiography in laparoscopic cholecystectomy - Hitoshi Saito; Shinichi Kinami; Kaori Maruyama; Yuta Sannomiya; Hiroyuki Takamura (BMJ Surgery, Interventions, & Health Technologies)
Objectives The advantages of indocyanine green (ICG) fluorescence cholangiography have been emphasized, but its disadvantages remain unclear. This study investigated the advantages and disadvantages of this modality, particularly the optimal timing of administration of ICG fluorescence.Design This was a retrospective analysis of prospectively collected patient data.Setting Data were gathered from a single institution.Participants 69 patients scheduled for cholecystectomy were included.Interventions We administered intravenous ICG injections at three different times: preoperatively (5 mg/body weight (BW), 15 min before incision), morning of the surgery (12.5 mg/BW 4 hours before surgery), and on the day before the surgery (25 mg/BW, 20 hours before surgery). The PINPOINT or SPY-PHI (Stryker) systems were used for fluorescence imaging.Main outcome measures The course of the common bile and cystic ducts was identified using fluorescence imaging. The visualization quality was graded on a three-point scale: good, poor, and unobservable.Results There were 17 patients for preoperative administration, 14 on the morning of the surgery, and 38 on the day before the surgery. The cystic duct could not be visualized in five patients because of insufficient dose, impacted gallstones, cystic duct stones, after endoscopic retrograde biliary drainage (ERBD), and severe cholecystitis. The observations were poor in 14 patients. The reasons for the poor visualization were cholecystitis after ERBD and a low signal-to-noise ratio due to intense light emission from the liver, which is a characteristic of preoperative administration.Conclusion The cystic and common bile ducts were well visualized using ICG fluorescence cholangiography, except in patients with impacted gallstones, cystic duct stones, ERBD, and severe cholecystitis. The most effective timing for ICG administration was the day before the surgery. ICG fluorescence cholangiography is not a substitute for intraoperative cholangiography or preoperative biliary imaging; however, it would be desirable in all patients who undergo cholecystectomy.Trial registration number jRCTs041180006.